The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1111/j.1365-2141.1981.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Platelet Aggregation Inhibitors in Tsetse (Glossina) Saliva with Studies of Roles of Thrombin and Citrate in in Vitro Platelet Aggregation

Abstract: Two inhibitors of platelet aggregation have been identified in saline extracts of Glossina morsitans (tsetse) salivary glands. A protein fraction (MW > 30 000) inhibited primary and secondary aggregation to ADP, secondary I aggregation to adrenalin, and aggregation to collagen. It also caused disaggregation of platelets stimulated by ADP and adrenalin. These properties could be explained by ADP hydrolytic activity. A previously identified antithrombin fraction (MW 11 000-13 000) abolished thrombin-induced aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 19 publications
(12 reference statements)
1
13
0
2
Order By: Relevance
“…However, molecular information on the individual tsetse salivary proteins and their biological activity remains scanty. Previous studies on Glossina morsitans saliva have reported the presence of a 11.3 kDa inhibitor of thrombin serine protease and esterase activities (Parker and Mant, 1979) and a 430 kDa protein fraction that inhibited the ADP-induced thrombocyte aggregation (Mant and Parker, 1981). In addition, a potent 32 AA blood meal-induced tsetse thrombin inhibitor (TTI), was characterised in salivary gland extracts.…”
Section: Introductionmentioning
confidence: 98%
“…However, molecular information on the individual tsetse salivary proteins and their biological activity remains scanty. Previous studies on Glossina morsitans saliva have reported the presence of a 11.3 kDa inhibitor of thrombin serine protease and esterase activities (Parker and Mant, 1979) and a 430 kDa protein fraction that inhibited the ADP-induced thrombocyte aggregation (Mant and Parker, 1981). In addition, a potent 32 AA blood meal-induced tsetse thrombin inhibitor (TTI), was characterised in salivary gland extracts.…”
Section: Introductionmentioning
confidence: 98%
“…Among the known tsetse saliva components are anti-hemostatic proteins [26], [27], [28], which include a potent anticoagulant thrombin inhibitor (TTI) [29], [30], and an anti-thrombotic apyrase (5′Nuclease) with dual inhibitory action that can bind to the fibrinogen receptor (GPIIb/IIIa) and inhibit ADP-induced platelet responses [31]. In addition, two abundant proteins (Tsal1 and Tsal2) have been described with DNA/RNA non-specific nucleic acid binding [26], [32], [33].…”
Section: Introductionmentioning
confidence: 99%
“…The biological role of the Tsal proteins could be in the digestive tract as well as at the feeding site where saliva proteins contribute to the generation of a local blood pool [3], [8], [9]. Feeding of tsetse flies on immunized mice with high titers of anti-Tsal IgGs did not affect their feeding performance [11].…”
Section: Discussionmentioning
confidence: 99%
“…During the probing and blood feeding interaction, tsetse flies inoculate a complex mixture of salivary components from which the composition has been explored by proteome and transcriptome analyses as well as by functional genomics approaches [1], [2], [3], [4], [5], [6], [7]. It has already been established that tsetse fly saliva interferes with host hemostatic reactions that are initiated at the blood feeding site [3], [8], [9]. Anti-coagulant and anti-thrombotic compounds include respectively the highly potent tsetse thrombin inhibitor [TTI, [8]] and a recently identified apyrase with fibrinogen receptor antagonistic features [3].…”
Section: Introductionmentioning
confidence: 99%